STUDI NUMERIK PENGARUH VARIASI CHORD BILAH TERHADAP PERFORMANSI TURBIN ANGIN HORISONTAL - Nu Rhahida Arini; Arizal Fatkhur Rakhman Sidiq; Amir Fadhilah; Prima Dwi Permatasari, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
Wind energy is one of the most promising renewable resources, harnessed through turbines and generators to produce electricity. Theefficiency of this energy conversion strongly depends on the aerodynamic performance of the turbine blades, which generate lift and drag forces. This study presents a numerical investigation on a modified Horizontal Axis Wind Turbine (HAWT) blade using Computational Fluid Dynamics (CFD) to enhance overall performance. The modifications are incoporated on NACA 0015 airfoils with non-uniform chord lengths and twist angles. The simulations are conducted using OpenFOAM to analyze two blade design variations, imcluding the original/unmodified NACA 0015 airfoil. Key performance indicators such as lift coefficient (CL), drag coefficient (CD), pressure contours, velocity distribution, and streamline flow patterns are evaluated to assess the effectiveness of modification. The results show that blades with non-uniform chord and twist angle distribution can improve power output by up to 19.8%. Furthermore, the study introduces the concept of blade localization for adaptive manufacturing and tolerance control, paving the way for more precise and efficient turbine production.